Proyectos de integración en América Latina durante el siglo XX : una mirada a la integración regional en el siglo XXI (2011)
ABSTRACT: From the nineteenth century, with the formation of the national states in Latin America, have promoted an integrationist projects unfinished. Nowadays, the need of the integration is highlighted between countries in different aspects: economic, political, military man, diplomat. The intention of the present article is to expose the reasons for which the “Pan Americanism” imposed by the United States turned into the principal obstacle for the consolidation of a true Latin-American project of integration during the first half of the twentieth century. Finally, after a tour of various attempts at integration in the second half of the twentieth century (observing the difficulties it has had historically the regional community), is to analyze the experience of the Mercosur as the more consolidated Latin-American integration project force in the beginning of the twenty-first century, in the economic area and, even, political.